Preparation process and application of medical material with high water condensation

By silanizing the sodium hyaluronate and combining it with porous amino starch, carboxymethylcellulose and antibacterial components, a highly condensed composite hydrogel material was prepared, which solved the existing hyaluronic acid hydrogel material. The problem of insufficient mechanical properties and moisturizing properties has achieved excellent mechanical properties, strong moisturizing properties and improved antibacterial and anti-inflammatory effects of the material.

CN119386252AActive Publication Date: 2025-02-07GUANGZHOU LVFANGZHOU IND CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410170609.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-06
Publication Date
2025-02-07
Estimated Expiration
2044-02-06

AI Technical Summary

Technical Problem

The mechanical properties and moisturizing properties of existing hyaluronic acid hydrogel materials are limited, and the antibacterial and anti-inflammatory properties need to be further improved.

Method used

Hypercoagulant composite hydrogel material was prepared by silanizing the sodium hyaluronate and combining with porous amino starch, carboxymethyl cellulose and antibacterial components. The material improves water retention through ultrasonic-microwave treatment, and improves mechanical properties and antibacterial and anti-inflammatory effects through multi-crosslinking network structure.

Benefits of technology

It achieves excellent mechanical properties, strong moisturizing properties and good antibacterial and anti-inflammatory effects of the material, and is suitable for medical dressings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a preparation process and application of a high-condensate medical material, sodium hyaluronate is subjected to silanization modification, so that the sodium hyaluronate has higher purity and moisturizing performance, then starch is subjected to porous treatment, the specific surface area of the starch is increased, more binding sites exist, and after the starch is subjected to amino modification, the water content of the starch is increased. In addition, a carboxymethyl cellulose and acrylamide gel solution is prepared, the porous amino starch / silanized sodium hyaluronate composite material and carboxymethyl cellulose are added into the gel solution, the gel solution is prepared, and the gel solution is prepared by adding the porous amino starch / silanized sodium hyaluronate composite material and the carboxymethyl cellulose into the gel solution. The medical dressing with excellent mechanical properties, strong moisture retention and better antibacterial and anti-inflammatory effects can be obtained after heating and forming.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical materials, and mainly relates to a preparation process and application of a medical material with high coagulation water, and in particular to a preparation process of a medical dressing with high coagulation water. Background Art

[0002] Hydrogel dressings have the advantages of good air permeability, high moisture retention, excellent mechanical properties and low sensitivity, and have a wide range of application potential in wound healing. Therefore, many scholars have studied hydrogel dressings. For example, in order to improve the protective ability and antibacterial properties of dressings on wounds, a biodegradable antibacterial medical hydrogel dressing was studied; in order to improve the moisturizing properties of hydrogel dressings, a variety of moisturizing ingredients were added during the preparation process, and substances such as glycerol were added to make the gel have good mechanical properties.

[0003] Hyaluronic acid (HA) is currently widely used in the fields of medical cosmetology and medical materials because it has important physiological functions such as maintaining extracellular space, regulating osmotic pressure, and lubrication. It can play an important biological function in wound healing, thereby reducing inflammatory response. In addition, it also has the characteristics of improving cell infiltration, scavenging free radicals and anti-oxidation.

[0004] Although HA has excellent properties such as good biocompatibility, high hydrophilicity and good adhesion, the mechanical properties and moisturizing properties of the prepared hydrogel are still limited. In addition, the antibacterial and anti-inflammatory properties need to be further improved. The hyaluronic acid structure contains chemical active sites such as hydroxyl and carboxyl groups, which can be chemically modified in various ways to give it specific functions. Hyaluronic acid derivatives have been reported to include acetylated hyaluronic acid, quaternized hyaluronic acid, carboxymethylated hyaluronic acid, silanized hyaluronic acid, etc. It has been reported in the literature that silanized hyaluronic acid has better moisturizing properties, no cytotoxicity, no skin irritation, and can promote the proliferation of keratinocytes. It can be used to prepare cosmetics and pharmaceutical excipients with skin moisturizing and repairing functions. However, the preparation method of silanized hyaluronic acid has rarely been reported.

[0005] Therefore, this paper carried out silanization modification on sodium hyaluronate and added a variety of antibacterial ingredients and water-locking structures into the dressing to prepare a highly water-coagulating medical material. Summary of the invention

[0006] The present invention relates to a preparation process and application of a medical material with high coagulation water. First, sodium hyaluronate is silanized and modified, and then starch is porous treated to increase the specific surface area of ​​starch, thereby having more binding sites. After the starch is amino-modified, the amino functional group can produce a stronger combination with functional groups such as hydrogen bonds. In addition, a carboxymethyl cellulose and acrylamide-based gel solution is prepared, and a porous amino starch / silanized sodium hyaluronate composite material and carboxymethyl cellulose are added to the gel solution. After it is heated and formed, a medical dressing with excellent mechanical properties, strong moisture retention and good antibacterial and anti-inflammatory effects can be obtained. The specific synthesis steps are as follows: S1. Preparation of modified sodium hyaluronate: 1-3 g of sodium hyaluronate is dissolved in 10-50 ml of N,N-dimethylformamide, 0.1-1 g of 1,1-dimethylol-silane-1-acetate is slowly added, and then 10-50 ul of hydrochloric acid with a mass fraction of 25-35 wt% is added dropwise, and then 5-10 mg of HMCM-22 molecular sieve is added, and stirred at 30-50 °C for 5-16 h. After the reaction is completed, 100-500 ml of anhydrous ethanol is poured into the reaction solution, and the substrate is washed and dried after the solution is precipitated to obtain silanized sodium hyaluronate; in this step, hydrochloric acid and molecular sieve are used as catalysts for the reaction, and both can provide protons during the reaction process, which effectively promotes the reaction, and the two different types of catalysts also play a synergistic role; the preparation method is controllable and green and environmentally friendly; the silanized sodium hyaluronate prepared in this step has the advantages of high purity, no irritation to the skin and high moisturizing performance; S2. Preparation of porous amino starch: weigh 10-20 g corn starch and place it in a three-necked flask, add 30-40 mL of 10% hydrochloric acid solution, heat and stir the obtained starch emulsion at 50-60 °C for 3-5 h, then use 1M Na2CO3 solution to neutralize the hydrochloric acid, and when the pH is neutral, continue stirring for 15-30 min, wash with deionized water 3-5 times to remove other impurities in the solution, and place the filtered product in a 50 °C drying oven to dry to obtain porous starch mpSt; dissolve 13-15 g porous starch in 15-20 mL epichlorohydrin containing 0.3-0.8 ml concentrated HCl, stir the mixture at 90-110 °C for 16-24 h, wash with anhydrous ethanol 3-5 times, and vacuum dry at 60 °C for use; dissolve 6-9 g halogenated starch in 50 mL 0.1 M sodium hydroxide, then add 10-15 g ethylenediamine is reacted at 60 °C for 24 h, and after the reaction is completed, it is continuously washed with anhydrous ethanol for 3-5 times, vacuum dried at 60 °C, and then ball milled with a ball mill to obtain porous amino starch with smaller particle size; in this step, the porous treatment of starch is beneficial to increase its specific surface area, and the porous structure is also beneficial to the attachment of other functional groups, thereby increasing the functional functional groups in the starch; the amino functional group and other functional groups can form a network structure such as hydrogen bond, which can play a role in locking water, and can also provide a certain antibacterial effect; the ball milling treatment makes the prepared material have a smaller size and can be better dispersed in other substances; S3. Preparation of porous amino starch / silanized sodium hyaluronate composite material: 0.5-2.5 g of the silanized sodium hyaluronate obtained in step S1 and 2.5-5 g of the porous amino starch obtained in step S2 are placed in a beaker, and then 30-50 ml of deionized water are added, and the two are evenly mixed using an ultrasonic-microwave method, and the ultrasonic conditions are 160 w and 5 min; in this step, after mixing the two, the composite material has high water retention, and the operation is simple, which improves the dispersion effect of the two; both starch and sodium hyaluronate have amino and hydroxyl functional groups, and the two substances can generate intermolecular forces, so that the dispersion is more uniform and the water content is higher; S4, preparation of carboxymethyl cellulose: placing waste straw in a grinder for crushing, placing 20-30 g of the crushed straw in a three-necked flask, pouring 5-8 g of sodium hydroxide and 60-80 ml of ethanol into the three-necked flask, stirring at 40°C for 3-5 h, adding 20-30 ml of chloroacetic acid, stirring at 60-80°C for 2.5-4.5 h, adding glacial acetic acid for neutralization, continuing to stir for 0.3-0.5 h, filtering and washing with ethanol, and drying to obtain carboxymethyl cellulose; the carboxymethyl cellulose prepared in this step contains a large number of hydrophilic groups, so it has a high water content. In addition, the use of waste straw as raw material realizes the secondary utilization of resources, is beneficial to environmental protection, and the raw materials are cheap and easy to obtain, which also reduces economic costs; S5. Preparation of acrylamide-based hydrogel solution: 3.05-3.85 g acrylamide AM, 0.015-0.025 g N,N-methylenebisacrylamide MBA and 0.02-0.03 g ammonium persulfate APS are placed in a beaker, and then 1-3 ml glycerol, 7-14 ml PBS buffer, 0.6-1.3 g curcumin and 0.2-0.8 g cinnamon essential oil are added and stirred for 15-30 min to obtain an acrylamide-based hydrogel solution. The acrylamide-based hydrogel solution prepared in this step can form a highly cross-linked network structure inside, which is beneficial to improving the mechanical effect of the gel. The addition of glycerol can improve the moisturizing properties of the material. The use of PBS buffer can provide more ions for the gel solution, so that the comprehensive performance of the gel is improved. In addition, the addition of curcumin and cinnamon essential oil gives the material anti-inflammatory and antibacterial properties, and because the two are different types of antibacterial components, the antibacterial effect is better improved after compounding. It is worth noting that this network structure with multiple cross-linking points can well fix curcumin, making it more stable. S6, preparation of high coagulation water composite hydrogel: 1.3-2.6g of the composite material prepared in step S3 and 1-2g of the carboxymethyl cellulose prepared in step S4 are added to the acrylamide-based hydrogel solution prepared in step S5, stirred for 10-30min, poured into a PTFE mold and placed in an oven at 50°C to obtain a high coagulation water composite hydrogel with a high cross-linked network; the high coagulation water composite hydrogel prepared in step S6 has a highly cross-linked network structure, because the materials used contain a large number of hydroxyl and amino functional groups, which can form hydrogen bonds with each other, and sodium ions can be used as cross-linking points, so the gel not only has a highly cross-linked network structure inside, but also exhibits higher mechanical properties and better moisturizing properties. In addition, since the gel structure is rich in amino functional groups and curcumin components, it also has a certain antibacterial effect and can be used as a medical dressing.

[0007] Preferably: in step S1, 2.68 g of sodium hyaluronate is dissolved in 35 ml of N,N-dimethylformamide.

[0008] Preferably, in step S1, 0.53 g of 1,1-dimethylol-silane-1-acetate, 25 ul of hydrochloric acid, and 10 mg of HMCM-22 molecular sieves are added, and the mixture is stirred at 50° C. for 12 h.

[0009] Preferably, in step S2, 15 g corn starch is weighed, 30 mL of 10% hydrochloric acid solution is added, and the mixture is heated and stirred at 60° C. for 5 h. After the pH reaches neutral, stirring is continued for 20 min.

[0010] Preferably: in step S2, 10 g of porous starch is dissolved in 20 mL of epichlorohydrin containing 0.6 ml of concentrated HCl, and the mixture is stirred at 110°C for 16 h; 6 g of halogenated starch is dissolved in 50 mL of 0.1 M sodium hydroxide, and then 10 g of ethylenediamine is added and reacted at 60°C for 24 h.

[0011] Preferably: in step S3, 2.13 g of the silanized sodium hyaluronate obtained in step S1 and 3.87 g of the porous amino starch obtained in step S2 are placed in a beaker, and then 50 ml of deionized water is added.

[0012] Preferably: in step S4, 20 g of crushed straw is taken, 5.6 g of sodium hydroxide and 80 ml of ethanol are added, and after stirring at 40° C. for 5 h, 20 ml of chloroacetic acid is added, and the mixture is stirred at 65° C. for 4 h. After neutralization, stirring is continued for 0.4 h.

[0013] Preferably: in step S5, 3.65 g acrylamide AM, 0.023 g N,N-methylenebisacrylamide MBA and 0.027 g ammonium persulfate APS are placed in a beaker, and then 2 ml of glycerol, 13 ml of PBS buffer, 0.75 g of curcumin and 0.3 g of cinnamon essential oil are added, and stirred for 30 min.

[0014] Preferably, in step S6, 2.5 g of the composite material prepared in step S3 and 2 g of the carboxymethyl cellulose prepared in step S4 are added to the acrylamide-based hydrogel solution prepared in step S5, and stirred for 30 min.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. In the present invention, hydrochloric acid and molecular sieve are used as catalysts for the reaction. Both of them can provide protons during the reaction, which effectively promotes the reaction, and the two different types of catalysts also play a synergistic role. The preparation method has controllable conditions and is green and environmentally friendly. The prepared silanized sodium hyaluronate has the advantages of high purity, no irritation to the skin and high moisturizing performance.

[0016] 2. The present invention performs porous treatment on starch, which is beneficial to increase its specific surface area. The porous structure is also beneficial to the attachment of other functional groups, thereby increasing the functional groups in the starch; the amino functional group and other functional groups can form a network structure such as hydrogen bonds, which can lock water and provide a certain antibacterial effect; the ball milling treatment makes the prepared material have a smaller size and can be better dispersed in other substances.

[0017] 3. The present invention performs ultrasonic-microwave treatment on porous amino starch and silanized sodium hyaluronate. After mixing the two, the composite material has high water retention and is simple to operate, thereby improving the dispersion effect of the two. Both starch and sodium hyaluronate have amino and hydroxyl functional groups, and intermolecular forces can be generated between the two substances, thereby being more evenly dispersed and having a higher water content.

[0018] 4. The carboxymethyl cellulose prepared by the present invention contains a large amount of hydrophilic groups, and therefore has a very high water content. In addition, the use of waste straw as raw material realizes the secondary utilization of resources, which is beneficial to environmental protection. The raw materials are cheap and easily available, and the economic cost is also reduced.

[0019] 5. A highly cross-linked network structure can be formed inside the acrylamide-based hydrogel solution prepared by the present invention, which is beneficial to improving the mechanical effect of the gel. The addition of glycerol can improve the moisture retention properties of the material. The use of PBS buffer can provide more ions for the gel solution, thereby improving the comprehensive performance of the gel. The addition of curcumin and cinnamon essential oil gives the material antibacterial properties, and since the two are different types of antibacterial components, the antibacterial effect is better improved after compounding. In addition, this compounding and adding method also gives the material a significant anti-inflammatory effect. It is worth noting that this network structure with multiple cross-linking points can well fix curcumin, making it more stable in exerting its effect.

[0020] 6. The high coagulation water composite hydrogel prepared by the present invention has a highly cross-linked network structure. This is because the materials used contain a large number of hydroxyl and amino functional groups, which can form hydrogen bonds with each other, and sodium ions can be used as cross-linking points. Therefore, the gel not only has a highly cross-linked network structure inside, but also exhibits high mechanical properties and good moisturizing properties. It is also found that the gel has a certain repair effect. In addition, since the gel structure is rich in amino functional groups and curcumin components, it also has a certain antibacterial effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0022] Figure 1 This is a diagram of the moisture retention of the gel materials prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention.

[0023] Figure 2 This is a microscopic morphology of starch in Comparative Example 3 of the present invention.

[0024] Figure 3 This is a microscopic morphology of the starch in Comparative Example 4 of the present invention.

[0025] Figure 4 This is a swelling data diagram of the gel materials prepared in Example 3 of the present invention and Comparative Example 5.

[0026] Figure 5 The antibacterial data diagram of the gel materials prepared in Example 4, Comparative Example 6 and Comparative Example 7 of the present invention. DETAILED DESCRIPTION

[0027] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the content of the present invention and are not used to limit the present invention.

[0028] Embodiment 1: S1. Preparation of modified sodium hyaluronate: 2.68 g of sodium hyaluronate was dissolved in 35 ml of N,N-dimethylformamide, 0.53 g of 1,1-dimethylol-silane-1-acetate was slowly added, and then 25 ul of hydrochloric acid with a mass fraction of 25-35 wt% was added dropwise, and then 10 mg of HMCM-22 molecular sieve was added, and stirred at 50 °C for 12 h. After the reaction was completed, 100-500 ml of anhydrous ethanol was poured into the reaction solution, and the substrate was washed and dried after the solution was precipitated to obtain silanized sodium hyaluronate; S2. Preparation of porous amino starch: weigh 15 g corn starch and place it in a three-necked flask, add 30 mL of 10% hydrochloric acid solution, heat and stir the obtained starch emulsion at 60 °C for 5 h, then use 1 M Na2CO3 solution to neutralize the hydrochloric acid, and when the pH is neutral, continue stirring for 20 min, wash with deionized water 3-5 times to remove other impurities in the solution, and place the filtered product in a 50 °C drying oven to dry to obtain porous starch mpSt; dissolve 10 g porous starch in 20 mL of epichlorohydrin containing 0.6 ml concentrated HCl, stir the mixture at 110 °C for 16 h, wash with anhydrous ethanol 3-5 times, and vacuum dry at 60 °C for use; dissolve 6 g halogenated starch in 50 mL 0.1 M sodium hydroxide, then add 10 g ethylenediamine and react at 60 °C for 24 h. After the reaction, continue washing with anhydrous ethanol 3-5 times and dry at 60 °C. The mixture was vacuum dried at ℃, and then ball-milled in a ball mill to obtain porous amino starch with smaller particle size; S3. Preparation of porous amino starch / silanized sodium hyaluronate composite material: 2.13 g of silanized sodium hyaluronate obtained in step S1 and 3.87 g of porous amino starch obtained in step S2 were placed in a beaker, and then 50 ml of deionized water were added, and the two were mixed evenly using an ultrasonic-microwave method, and the ultrasonic conditions were 160 w and 5 min; S4, preparation of carboxymethyl cellulose: waste straw is placed in a grinder for crushing, 20 g of the crushed straw is placed in a three-necked flask, 5.6 g of sodium hydroxide and 80 ml of ethanol are poured into the three-necked flask, 20 ml of chloroacetic acid is added after stirring at 40°C for 5 h, glacial acetic acid is added after stirring at 65°C for 4 h for neutralization, stirring is continued for 0.4 h, ethanol is used for filtering and washing, and carboxymethyl cellulose is obtained after drying; S5. Preparation of acrylamide-based hydrogel solution: 3.65 g acrylamide AM, 0.023 g N,N-methylenebisacrylamide MBA and 0.027 g ammonium persulfate APS were placed in a beaker, and then 2 ml glycerol, 13 ml PBS buffer, 0.75 g curcumin and 0.3 g cinnamon essential oil were added and stirred for 30 min to obtain an acrylamide-based hydrogel solution; S6. Preparation of high coagulation water composite hydrogel: Take 2.5g of the composite material prepared in step S3 and 2g of carboxymethyl cellulose prepared in step S4, add them to the acrylamide-based hydrogel solution prepared in step S5, stir for 30 minutes, pour it into a PTFE mold and put it into an oven at 50°C to obtain a high coagulation water composite hydrogel with a high cross-linked network; the hydrogel has a certain antibacterial effect and can be used as a medical dressing.

[0029] Comparative Example 1: Except that hydrochloric acid is not added in step S1, the remaining steps are the same as those in Example 1.

[0030] Comparative Example 2: Except that HMCM-22 molecular sieve is not added in step S1, the remaining steps are the same as those in Example 1.

[0031] Figure 1 The moisture retention graphs of the gel materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention are shown in FIG. Figure 1 It can be seen that Example 1 has a more lasting moisturizing property. This is because the sodium hyaluronate used in Example 1 has a higher degree of silanization modification and has many characteristic functional groups in its molecular structure, so the modified sodium hyaluronate has higher purity and stronger moisturizing effect.

[0032] Embodiment 2: S1. Preparation of modified sodium hyaluronate: 1.69 g of sodium hyaluronate was dissolved in 30 ml of N,N-dimethylformamide, 0.31 g of 1,1-dimethylol-silane-1-acetate was slowly added, and 10 ul of hydrochloric acid with a mass fraction of 25-35 wt% was added dropwise, and then 5 mg of HMCM-22 molecular sieve was added, and stirred at 50 °C for 10 h. After the reaction was completed, 100-500 ml of anhydrous ethanol was poured into the reaction solution, and the substrate was washed and dried after the solution was precipitated to obtain silanized sodium hyaluronate; S2. Preparation of porous amino starch: 15 g corn starch was weighed and placed in a three-necked flask, 30 mL of 10% hydrochloric acid solution was added, the obtained starch emulsion was heated and stirred at 60 °C for 3 h, and then the hydrochloric acid was neutralized with 1 M Na2CO3 solution. When the pH was neutral, stirring was continued for 30 min, and the solution was washed with deionized water for 3-5 times to remove other impurities in the solution. The product after filtration was placed in a 50 °C drying oven for drying to obtain porous starch mpSt; 10 g porous starch was dissolved in 15 mL of epichlorohydrin containing 0.5 ml concentrated HCl, the mixture was stirred at 90 °C for 24 h, washed with anhydrous ethanol for 3-5 times, and vacuum dried at 60 °C for use; 8.2 g halogenated starch was dissolved in 50 mL of 0.1 M sodium hydroxide, and then 10.8 g ethylenediamine was added to react at 60 °C for 24 h. After the reaction, it was continued to be washed with anhydrous ethanol for 3-5 times and dried at 60 °C. The mixture was vacuum dried at ℃, and then ball-milled in a ball mill to obtain porous amino starch with smaller particle size; S3. Preparation of porous amino starch / silanized sodium hyaluronate composite material: 1.32 g of silanized sodium hyaluronate obtained in step S1 and 4.68 g of porous amino starch obtained in step S2 were placed in a beaker, and then 30 ml of deionized water were added, and the two were mixed evenly using an ultrasonic-microwave method, and the ultrasonic conditions were 160 w and 5 min; S4, preparation of carboxymethyl cellulose: waste straw is placed in a grinder for crushing, 20 g of the crushed straw is placed in a three-necked flask, 5 g of sodium hydroxide and 60 ml of ethanol are poured into the three-necked flask, 20 ml of chloroacetic acid is added after stirring at 40°C for 3 h, glacial acetic acid is added after stirring at 60°C for 2.5 h for neutralization, stirring is continued for 0.3 h, ethanol is used for filtering and washing, and carboxymethyl cellulose is obtained after drying; S5. Preparation of acrylamide-based hydrogel solution: 3.05 g acrylamide AM, 0.015 g N,N-methylenebisacrylamide MBA and 0.02 g ammonium persulfate APS were placed in a beaker, and then 3 ml glycerol, 12 ml PBS buffer, 0.6 g curcumin and 0.2 g cinnamon essential oil were added and stirred for 30 min to obtain an acrylamide-based hydrogel solution; S6. Preparation of high coagulation water composite hydrogel: Take 1.3 g of the composite material prepared in step S3 and 1 g of carboxymethyl cellulose prepared in step S4, add them to the acrylamide-based hydrogel solution prepared in step S5, stir for 30 min, pour it into a PTFE mold and put it into an oven at 50°C to obtain a high coagulation water composite hydrogel with a high cross-linked network; the hydrogel has a certain antibacterial effect and can be used as a medical dressing.

[0033] Comparative Example 3: Except that the starch is not subjected to porous treatment in step S2, the remaining steps are the same as those in Example 2.

[0034] Comparative Example 4: Except that the porous starch is not amino-modified in step S2, the remaining steps are the same as those in Example 2.

[0035] Figure 2 This is a microscopic morphology of starch prepared in Comparative Example 3 of the present invention. Figure 3 This is a microscopic morphology of starch prepared in Comparative Example 4 of the present invention. Figure 2 It can be seen that the starch surface is smooth. Figure 3 It can be seen that the starch surface is destroyed and presents a porous structure. The porous structure increases the specific surface area of ​​the starch and provides more sites, which is conducive to the combination with amino groups, thereby improving the comprehensive performance of the composite material.

[0036] Embodiment 3: S1. Preparation of modified sodium hyaluronate: 2.96 g of sodium hyaluronate was dissolved in 30 ml of N,N-dimethylformamide, 0.14 g of 1,1-dimethylol-silane-1-acetate was slowly added, and 30 ul of hydrochloric acid with a mass fraction of 25-35 wt% was added dropwise, and then 7 mg of HMCM-22 molecular sieve was added, and stirred at 50 °C for 14 h. After the reaction was completed, 100-500 ml of anhydrous ethanol was poured into the reaction solution, and the substrate was washed and dried after the solution was precipitated to obtain silanized sodium hyaluronate; S2. Preparation of porous amino starch: 18.6 g corn starch was weighed and placed in a three-necked flask, 35 mL of 10% hydrochloric acid solution was added, the obtained starch emulsion was heated and stirred at 60 °C for 3 h, and then the hydrochloric acid was neutralized with 1 M Na2CO3 solution. When the pH was neutral, stirring was continued for 30 min, and the solution was washed with deionized water for 3-5 times to remove other impurities in the solution. The filtered product was placed in a 50 °C drying oven for drying to obtain porous starch mpSt; 13.8 g porous starch was dissolved in 20 mL epichlorohydrin containing 0.6 ml concentrated HCl, the mixture was stirred at 110 °C for 18 h, washed with anhydrous ethanol for 3-5 times, and vacuum dried at 60 °C for standby use; 8.7 g halogenated starch was dissolved in 50 mL 0.1 M sodium hydroxide, and then 10.3 g ethylenediamine was added and reacted at 60 °C for 24 h. h, after the reaction is completed, continue to wash with anhydrous ethanol for 3-5 times, vacuum dry at 60 ° C, and then use a ball mill to perform ball milling to obtain porous amino starch with smaller particle size; S3. Preparation of porous amino starch / silanized sodium hyaluronate composite material: 2.31 g of silanized sodium hyaluronate obtained in step S1 and 4.69 g of porous amino starch obtained in step S2 were placed in a beaker, and then 50 ml of deionized water were added, and the two were mixed evenly using an ultrasonic-microwave method, and the ultrasonic conditions were 160 w and 5 min; S4, preparation of carboxymethyl cellulose: waste straw is placed in a grinder for crushing, 25 g of the crushed straw is placed in a three-necked flask, 6 g of sodium hydroxide and 80 ml of ethanol are poured into the three-necked flask, 20 ml of chloroacetic acid is added after stirring at 40°C for 3 h, glacial acetic acid is added after stirring at 60°C for 3 h for neutralization, stirring is continued for 0.3-0.5 h, ethanol is used for filtering and washing, and carboxymethyl cellulose is obtained after drying; S5. Preparation of acrylamide-based hydrogel solution: 3.25 g acrylamide AM, 0.015 g N,N-methylenebisacrylamide MBA and 0.02 g ammonium persulfate APS were placed in a beaker, and then 3 ml glycerol, 14 ml PBS buffer, 0.62 g curcumin and 0.28 g cinnamon essential oil were added and stirred for 30 min to obtain an acrylamide-based hydrogel solution; S6. Preparation of high coagulation water composite hydrogel: Take 1.37 g of the composite material prepared in step S3 and 1.23 g of carboxymethyl cellulose prepared in step S4, add them to the acrylamide-based hydrogel solution prepared in step S5, stir for 30 min, pour it into a PTFE mold and put it into an oven at 50°C to obtain a high coagulation water composite hydrogel with a high cross-linked network; the hydrogel has a certain antibacterial effect and can be used as a medical dressing.

[0037] Comparative Example 5: Except that chloroacetic acid is not added in step S4, the remaining steps are the same as those in Example 3.

[0038] The swelling rate of the sample is analyzed by testing the mass of the sample before and after complete swelling. Figure 4 The swelling data of the gel material prepared in Example 3 and Comparative Example 5 of the present invention are shown in FIG. Figure 4 It can be seen that the material prepared in Example 3 has better swelling properties. This is because its structure contains carboxymethyl, which has a good combination with amino, hydroxyl and other functional groups. In addition, the close connection of the internal structure greatly improves the water absorption and moisture retention of the material.

[0039] Embodiment 4: S1. Preparation of modified sodium hyaluronate: 2.72 g of sodium hyaluronate was dissolved in 30 ml of N,N-dimethylformamide, 0.18 g of 1,1-dimethylol-silane-1-acetate was slowly added, and 10 ul of hydrochloric acid with a mass fraction of 25-35 wt% was added dropwise, and then 5 mg of HMCM-22 molecular sieve was added, and stirred at 50 °C for 15 h. After the reaction was completed, 100-500 ml of anhydrous ethanol was poured into the reaction solution, and the substrate was washed and dried after the solution was precipitated to obtain silanized sodium hyaluronate; S2. Preparation of porous amino starch: 16 g corn starch was weighed and placed in a three-necked flask, 40 mL of 10% hydrochloric acid solution was added, the obtained starch emulsion was heated and stirred at 60 °C for 5 h, and then the hydrochloric acid was neutralized with 1 M Na2CO3 solution. When the pH was neutral, stirring was continued for 30 min, and the solution was washed with deionized water for 3-5 times to remove other impurities in the solution. The filtered product was placed in a 50 °C drying oven for drying to obtain porous starch mpSt; 13 g porous starch was dissolved in 20 mL of epichlorohydrin containing 0.7 ml concentrated HCl, the mixture was stirred at 90 °C for 16 h, washed with anhydrous ethanol for 3-5 times, and vacuum dried at 60 °C for standby use; 8.6 g halogenated starch was dissolved in 50 mL 0.1 M sodium hydroxide, and then 10.4 g ethylenediamine was added to react at 60 °C for 24 h. After the reaction, it was continued to be washed with anhydrous ethanol for 3-5 times and dried at 60 °C. The mixture was vacuum dried at ℃, and then ball-milled in a ball mill to obtain porous amino starch with smaller particle size; S3. Preparation of porous amino starch / silanized sodium hyaluronate composite material: 2.36 g of silanized sodium hyaluronate obtained in step S1 and 4.64 g of porous amino starch obtained in step S2 were placed in a beaker, and then 30 ml of deionized water were added, and the two were mixed evenly using an ultrasonic-microwave method, and the ultrasonic conditions were 160 w and 5 min; S4, preparation of carboxymethyl cellulose: waste straw is placed in a grinder for crushing, 20 g of the crushed straw is placed in a three-necked flask, 5 g of sodium hydroxide and 60 ml of ethanol are poured into the three-necked flask, 20 ml of chloroacetic acid is added after stirring at 40°C for 3 h, glacial acetic acid is added for neutralization after stirring at 80°C for 3 h, stirring is continued for 0.3 h, ethanol is used for filtering and washing, and carboxymethyl cellulose is obtained after drying; S5. Preparation of acrylamide-based hydrogel solution: 3.25 g acrylamide AM, 0.015 g N,N-methylenebisacrylamide MBA and 0.023 g ammonium persulfate APS were placed in a beaker, and then 3 ml glycerol, 12 ml PBS buffer, 0.64 g curcumin and 0.26 g cinnamon essential oil were added and stirred for 30 min to obtain an acrylamide-based hydrogel solution; S6. Preparation of high coagulation water composite hydrogel: 1.95 g of the composite material prepared in step S3 and 1.85 g of carboxymethyl cellulose prepared in step S4 are added to the acrylamide-based hydrogel solution prepared in step S5. After stirring for 30 minutes, the mixture is poured into a PTFE mold and placed in an oven at 50°C to obtain a high coagulation water composite hydrogel with a highly cross-linked network. The hydrogel has a certain antibacterial effect and can be used as a medical dressing.

[0040] Comparative Example 6: Except that cinnamon essential oil is not added in step S5, the remaining steps are the same as those in Example 4.

[0041] Comparative Example 7: Except that curcumin is not added in step S5, the remaining steps are the same as those in Example 4.

[0042] Antibacterial test method: Take 20 uL of frozen E. coli and inoculate it into the sterilized LB liquid culture medium, incubate it in a biological shaker for 4 hours and 12 hours to obtain activated bacteria. Put different gels of 0.5x3 cm into 50 ml centrifuge tubes (the centrifuge tubes are sterilized by ultraviolet light), add 5 ml of sterile water and 1 ml of E. coli suspension, and shake to disperse evenly. Put different centrifuge tubes containing samples into a biological incubator for culture. After 12, 24 and 36 hours of bacterial culture, take out the quantitative suspension and put it into a sterile 96-well plate, and then use an enzyme marker to measure the value of the suspension at 600 nm.

[0043] Figure 5 The antibacterial data of the gel materials prepared in Example 4, Comparative Example 6 and Comparative Example 7 of the present invention are shown in FIG. Figure 5 It can be seen that the gel material itself has no significant antibacterial effect, but the antibacterial effect of Example 4 after compounding is very obvious, while Comparative Examples 6 and 7 also have antibacterial effects, but their effects are weaker. This may be because the two components of cinnamon essential oil and curcumin exist in the gel of Example 4 at the same time. Due to the special spatial conformation and fixation, the antibacterial effect of these two substances is greatly promoted, and the three play a significant synergistic role.

[0044] The above-mentioned embodiments only express the specific implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for those skilled in the art, without departing from the concept of the present invention, any other replacement, simplification and other substitution methods made without departing from the principle of the present invention are within the protection scope of the present invention.

Claims

1. A process for preparing a medical material with high condensation water, characterized in that: The specific synthesis steps are as follows: S1. Preparation of modified sodium hyaluronate: 1-3 g of sodium hyaluronate is dissolved in 10-50 ml of N,N-dimethylformamide, 0.1-1 g of 1,1-dimethylol-silane-1-acetate is slowly added, and then 10-50 ul of hydrochloric acid with a mass fraction of 25-35 wt% is added dropwise, and then 5-10 mg of HMCM-22 molecular sieve is added, and stirred at 30-50 °C for 5-16 h. After the reaction is completed, 100-500 ml of anhydrous ethanol is poured into the reaction solution, and the substrate is washed and dried after the solution is precipitated to obtain silanized sodium hyaluronate; S2. Preparation of porous amino starch: weigh 10-20 g corn starch and place it in a three-necked flask, add 30-40 mL of 10% hydrochloric acid solution, heat and stir the obtained starch emulsion at 50-60 °C for 3-5 h, then use 1 M Na2CO3 solution to neutralize the hydrochloric acid, and when the pH is neutral, continue stirring for 15-30 min, wash with deionized water 3-5 times to remove other impurities in the solution, and place the filtered product in a 50 °C drying oven to dry to obtain porous starch mpSt; dissolve 13-15 g porous starch in 15-20 mL epichlorohydrin containing 0.3-0.8 ml concentrated HCl, stir the mixture at 90-110 °C for 16-24 h, wash with anhydrous ethanol 3-5 times, and vacuum dry at 60 °C for use; dissolve 6-9 g halogenated starch in 50 mL 0.1 M sodium hydroxide, then add 10-15 g ethylenediamine was reacted at 60 °C for 24 h, and then washed with anhydrous ethanol for 3-5 times, dried in vacuum at 60 °C, and then ball-milled with a ball mill to obtain porous amino starch with smaller particle size; S3. Preparation of porous amino starch / silanized sodium hyaluronate composite material: 0.5-2.5 g of silanized sodium hyaluronate obtained in step S1 and 2.5-5 g of porous amino starch obtained in step S2 are placed in a beaker, and then 30-50 ml of deionized water are added, and the two are mixed evenly using an ultrasonic-microwave method, and the ultrasonic conditions are 160 w, 5 min; S4, preparation of carboxymethyl cellulose: placing waste straw in a grinder for crushing, placing 20-30 g of the crushed straw in a three-necked flask, pouring 5-8 g of sodium hydroxide and 60-80 ml of ethanol into the three-necked flask, stirring at 40°C for 3-5 h, adding 20-30 ml of chloroacetic acid, stirring at 60-80°C for 2.5-4.5 h, adding glacial acetic acid for neutralization, continuing to stir for 0.3-0.5 h, filtering and washing with ethanol, and drying to obtain carboxymethyl cellulose; S5. Preparation of acrylamide-based hydrogel solution: 3.05-3.85 g acrylamide AM, 0.015-0.025 g N,N-methylenebisacrylamide MBA and 0.02-0.03 g ammonium persulfate APS are placed in a beaker, and then 1-3 ml glycerol, 7-14 ml PBS buffer, 0.6-1.3 g curcumin and 0.2-0.8 g cinnamon essential oil are added and stirred for 15-30 min to obtain an acrylamide-based hydrogel solution; S6. Preparation of high coagulation water composite hydrogel: 1.3-2.6 g of the composite material prepared in step S3 and 1-2 g of carboxymethyl cellulose prepared in step S4 are added to the acrylamide-based hydrogel solution prepared in step S5, stirred for 10-30 min, poured into a PTFE mold and placed in an oven at 50° C. to obtain a high coagulation water medical material.

2. The process for preparing a medical material with high condensation water according to claim 1, characterized in that: In step S1, 2.68 g of sodium hyaluronate was dissolved in 35 ml of N,N-dimethylformamide.

3. The process for preparing a medical material with high condensation water according to claim 2, characterized in that: In the step S1, 0.53 g of 1,1-dimethylol-silane-1-acetate, 25 ul of hydrochloric acid, and 10 mg of HMCM-22 molecular sieves were added, and the mixture was stirred at 50° C. for 12 h.

4. The process for preparing a medical material with high condensation water according to claim 3, characterized in that: In step S2, 15 g corn starch was weighed, 30 mL of 10% hydrochloric acid solution was added, and the mixture was heated and stirred at 60° C. for 5 h. After the pH was neutral, stirring was continued for 20 min.

5. The process for preparing a medical material with high coagulation water according to claim 3, characterized in that: In step S2, 10 g of porous starch is dissolved in 20 mL of epichlorohydrin containing 0.6 ml of concentrated HCl, and the mixture is stirred at 110° C. for 16 h; 6 g of halogenated starch is dissolved in 50 mL of 0.1 M sodium hydroxide, and then 10 g of ethylenediamine is added and reacted at 60° C. for 24 h.

6. The process for preparing a medical material with high condensation water according to claim 5, characterized in that: In step S3, 2.13 g of the silanized sodium hyaluronate obtained in step S1 and 3.87 g of the porous amino starch obtained in step S2 are placed in a beaker, and then 50 ml of deionized water is added.

7. The process for preparing a medical material with high coagulation water according to claim 6, characterized in that: In step S4, 20 g of the crushed straw was taken, 5.6 g of sodium hydroxide and 80 ml of ethanol were added, and the mixture was stirred at 40° C. for 5 h, then 20 ml of chloroacetic acid was added, and the mixture was stirred at 65° C. for 4 h. After neutralization, the mixture was stirred for 0.4 h.

8. The process for preparing a medical material with high coagulation water according to claim 7, characterized in that: In step S5, 3.65 g acrylamide AM, 0.023 g N,N-methylenebisacrylamide MBA and 0.027 g ammonium persulfate APS were placed in a beaker, and then 2 ml glycerol, 13 ml PBS buffer, 0.75 g curcumin and 0.3 g cinnamon essential oil were added and stirred for 30 min.

9. The process for preparing a medical material with high condensation water according to claim 8, characterized in that: In step S6, 2.5 g of the composite material prepared in step S3 and 2 g of the carboxymethyl cellulose prepared in step S4 are added to the acrylamide-based hydrogel solution prepared in step S5, and stirred for 30 min.

10. The medical material with high coagulation water prepared according to claims 1-9.

Citation Information

Patent Citations

  • Hydrogel active dressing with antibacterial and anti-inflammatory functions

    CN112370567A

  • Antibacterial and hemostatic silica gel dressing and preparation process thereof

    CN116549724A

  • Skin care mask using hydrogel containing arazyme

    KR1020110008648A

  • Hydrogel particle and method for producing same, cell or cell structure each enclosing hydrogel particle therein, method for evaluating activity of cell using hydrogel particle, and use of hydrogel particle as sustained release preparation

    US20200338218A1

  • Process for preparing hydrogel component-containing composition, and use thereof

    WO2006043552A1